Analisis Pengungkapan Biaya Aktivitas Pertambangan pada Perusahaan Pertambangan yang Terdaftar di BEI terhadap Return On Investment - Gregorius Adhytama Krishantoro (EXERO : Journal of Research in Business and Economics, 2019)
This study was conducted to analyze the relationship that arises from the disclosure of costs for exploration activities, development and construction, production, and environmental management with Return on Investment (ROI) in mining companies listed in Indonesia Stock Exchange (IDX). The type of this research is an empirical study. The data used in the study was ordinal data. The data obtained through the documentation of the consolidated financial statements. Data analysis techniques used were checklists, Kolmogorov-Smirnov normality test and Pearson correlation test. The results show that the disclosure of costs for mining activities (exploration, development and construction, production, and environmental management) has a weakening relationship with Return on Investment. The relationship between the two variables is inversely proportional, which means if the level of cost disclosure is more increasing, the ROI level in the company will getting lower.